Innovative practices in student teaching of some teacher training institutions in the Philippines and their implications to the Academy for Teacher Educators Kabul, Afghanistan - Saleem, Abdul Kadir 1935-
This study attempted to find out what some teacher training institutions do to produce teachers who can teach effectively. It focuses on student teaching. Perceptions of respondents were gathered with the use of three sets of questionnaires. Based on the respondents' perceptions of the inadequacy of the present student teaching program and the needs and resources of the country, a new student teaching program was proposed. Outstanding features were: that the post graduate course be extended to two years; that the content of the program be community-oriented; that teachers undergo further training; that more and modern facilities be installed; and that on-campus and off-campus teaching experiences be structured to provide a wider and more variated scheme of learning.